Successful conversion therapy for unresectable hepatocellular carcinoma is getting closer: A systematic review and meta-analysis - Pei, Yinxuan; Li, Weiwei; Wang, Zixiang; Liu, Jinlong (Frontiers in Oncology, 2022)
Background: Conversion therapy provides selected patients with unresectable hepatocellular carcinoma the opportunity to undergo a curative hepatectomy and achieve long-term survival. Although various regimens have been used for conversion therapy, their conversion rate and safety remain uncertain. Therefore, we conducted some meta-analyses to evaluate the efficacy and safety of several conversion regimens in order to elucidate the optimal regimen. Method: We performed systematic literature research on PubMed, Embase, and the Web of Science until July 30, 2022. Chemotherapy, transcatheter arterial chemoembolization (TACE), molecular therapy (targeted therapy, immunotherapy, or a combination of both), and combined locoregional-systemic therapy were the conversion regimens we targeted. Results: Twenty-four studies were included. The pooled conversion rates for chemotherapy, TACE, molecular therapy, and combined locoregional-systemic therapy were 13% (95% confidence interval [CI], 7%–20%; I² = 82%), 12% (95% CI, 9%–15%; I² = 60%), 10% (95% CI, 3%–20%; I² = 90%), and 25% (95% CI, 13%–38%; I² = 89%), respectively. The pooled objective response rates (ORR) for chemotherapy, TACE, molecular therapy, and combined locoregional-systemic therapy were 19% (95% CI, 12%–28%; I² = 77%), 32% (95% CI, 15%–51%; I² = 88%), 30% (95% CI, 15%–46%; I² = 93%), and 60% (95% CI, 41%–77%; I² = 91%), respectively. The pooled grade ≥3 AEs for chemotherapy, TACE, molecular therapy, and combined locoregional-systemic therapy were 67% (95% CI, 55%–78%; I² = 79%), 34% (95% CI, 8%–66%; I²= 92%), 30% (95% CI, 18%–43%; I² = 84%), and 40% (95% CI, 23%–58%; I² = 89%), respectively. Subgroup analyses showed the conversion rate, ORR and grade ≥3 AE rate for tyrosine kinase inhibitor (TKI) combined with immune checkpoint inhibitor (ICI) and locoregional therapy (LRT) were 33% (95% CI, 17%-52%; I² = 89%), 73% (95% CI, 51%–91%; I² = 90%), 31% (95% CI, 10%-57%; I² = 89%), respectively. Conclusion: Combined locoregional-systemic therapy, especially TKI combined with ICI and LRT, may be the most effective conversion therapy regimen, associated with a significant ORR, conversion potential, and an acceptable safety profile.